Pemetaan Potensi Panas Bumi Menggunakan Penginderaan Jauh dan Analisis Multikriteria Berbasis AHP di Surian, Kabupaten Solok, Sumatera Barat - Khairunnisa; Elistia Liza Namigo (Jurnal Fisika Unand, 2026)
This research was conducted in Surian, Solok Regency, West Sumatra, which is located in the active magmatic zone of the Barisan Mountains and is believed to have geothermal potential. The main objective of this study was to identify areas with potential geothermal resources using remote sensing data and spatial analysis methods. The parameters used included the Normalized Difference Vegetation Index (NDVI) from Sentinel-2 imagery, Land Surface Temperature (LST) from Landsat-8 imagery, and Fault Fracture Density (FFD) from SRTM DEM data. The data were processed using Google Earth Engine (GEE) and QGIS 3.34, and the combined analysis of the three parameters was carried out using the Analytical Hierarchy Process (AHP) method. The results showed that the NDVI values ​​ranged from –0.1907 to 0.9117, the LST between 13.4 °C and 32.9 °C, and the FFD between 0.001 and 3.474. These values ​​were generally concentrated around the main fault zone, particularly in the central to western part of the study area. A geothermal potential map was successfully created, dividing the regions into three categories: low, medium, and high. This map also helped identify several areas with potential, but without clear manifestations on the surface. In conclusion, this study demonstrates that combining NDVI, LST, and FFD parameters with spatial analysis is a method that can support geothermal exploration.